Genetic selection and breeding practices of Kansas Holstein herds in relation to yearly level of production - Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1985)
An analysis of 41,426 cows in 635 Kansas Holstein herds indicated that considerable improvement can be made in genetic gain by more stringent sire selection and greater use of proved bulls. The generation interval in dairy cattle is about 5 yr so a dairy producer has only a limited number of decisions by which to make genetic improvement. Maximum genetic gain is possible by breeding 80 percent of the herd to bulls in the 80+ percentile. The remainder of the herd should be bred to several young sires in a progeny test program to aid in selecting the meritorious sires of the next generation. All heifers should be bred to superior bulls using calving ease as an additional selection criterion.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Genetic selection; Breeding; Production